Ruiz Figueroa, Manuel (coord), El islam y Occidente desde América Latina, México, El Colegio de México, 2007, 319 pp. - Taboada, Hernán G. H. (Estudios de Asia y África, 2008)
Ruiz Figueroa, Manuel (coord), El islam y Occidente desde América Latina, México, El Colegio de México, 2007, 319 pp.